Mitochondrial dynamic alterations regulate melanoma cell progression. Issue 2 (6th September 2018) - Dal Yontem, Fulya; Kim, Sun‐Hee; Ding, Zhen; Grimm, Elizabeth; Ekmekcioglu, Suhendan; Akcakaya, Handan
Abstract: Research on mitochondrial fusion and fission (mitochondrial dynamics) has gained much attention in recent years, as it is important for understanding many biological processes, including the maintenance of mitochondrial functions, apoptosis, and cancer. The rate of mitochondrial biosynthesis and degradation can affect various aspects of tumor progression. However, the role of mitochondrial dynamics in melanoma progression remains controversial and requires a mechanistic understanding to target the altered metabolism of cancer cells. Therefore, in our study, we disrupted mitochondrial fission with mdivi‐1, the reported inhibitor of dynamin related protein 1 (Drp1), and knocked down Drp1 and Mfn2 to evaluate the effects of mitochondrial dynamic alterations on melanoma cell progression. Our confocal study results showed that mitochondrial fission was inhibited both in mdivi‐1 and in Drp1 knockdown cells and, in parallel, mitochondrial fusion was induced. We also found that mitochondrial fission inhibition by mdivi‐1 induced cell death in melanoma cells. However, silencing Drp1 and Mfn2 did not affect cell viability, but enhanced melanoma cell migration. We further show that dysregulated mitochondrial fusion by Mfn2 knockdowns suppressed the oxygen consumption rate of melanoma cells. Together, our findings suggest that mitochondrial dynamic alterations regulate melanoma cell migration and progression. Abstract : Our study interrogates the role of mitochondrial dynamics in melanoma cell viability, migration, and energy metabolism to better understand its therapeutic potential.